The Ecological and Ethical Consumption Development Prospects in Poland Compared with the Western European Countries - Koszewska, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2011)
An overview of the Western European literature shows that one of the most distinct trends in consumption that has been noted in the recent years is globally increasing environmental and social awareness. The issue of consumers' behaviours and attitudes towards "socially responsible products" has been gaining importance in Polish economy as well. This article evaluates the development prospects of ethical and ecological consumption in Poland vis-a-vis Western European countries. The comparative analysis being part of the article utilizes primary sources of information, i.e. interviews with a representative sample of Polish adults, as well as secondary sources of information. A factor analysis or, more precisely, a principal component analysis, allowed dividing Polish consumers into groups that were typologically homogeneous in respect of their sensitivity to various aspects of business ethics and ecology.